A SCIENTIFIC APPROACH TO PICTORIAL REMINISCE IN IRIS MURDOCH'S NOVEL THE UNICORN - Kurbanova, Muxabbat (Журнал иностранных языков и лингвистики, 2023)
Our article on Iris Murdoch's novel The Unicorn comes from the prism of pictorial memories of Flemish tapestries of the 15 chronotropic contradictions to clarify illusion and reality.